Patients' and clinicians' views of the psychological components of tinnitus treatment that could inform audiologists’ usual care: a Delphi survey - Thompson, Dean M.; Taylor, John A.; Hall, Deborah A.; Walker, Dawn-Marie; McMurran, Mary; Casey, Amanda; Stockdale, David; Featherstone, Debbie; Hoare, Derek J. (Lippincott, Williams & Wilkins, 2017)
Background Tinnitus is a phantom auditory sensation typified by subjective reports of a ringing or buzzing noise, and is associated with reduced quality of life and functional health status. Psychological therapies delivered by psychologists have been found to improve tinnitus-related distress, and although some audiologists deliver psychological interventions, these are not standardized in the UK. There is a lack of clinical psychologists to provide this care, and the remit of the audiologist in the UK has expanded to meet this need. This study provides data on the components of psychological therapies from the literature that patients and clinicians consider may usefully inform audiologists’ usual care for tinnitus. Objectives The aim of this study was to determine which components of psychological therapies are most important and appropriate to inform audiologists’ usual care for people with tinnitus. Design A 39-member panel of patients, audiologists, hearing therapists, and psychologists completed a 3-round Delphi survey to reach consensus on essential components of audiologist-delivered psychologically informed care for tinnitus. Results Consensus (≥ 80% agreement) was reached on including 76 of 160 components. No components reached consensus for exclusion. The components reaching consensus were predominantly common therapeutic skills such as Socratic questioning and active listening, rather than specific techniques, for example, graded exposure therapy or cognitive restructuring. Consensus on educational components to include largely concerned psychological models of tinnitus rather than neurophysiological information. Conclusions The results of this Delphi survey provide a tool to develop audiologists’ usual tinnitus care using components that both patients and clinicians agree are important and appropriate to be delivered by an audiologist for adults with tinnitus-related distress. Research is now necessary to test the added effects of these components when delivered by audiologists.